Penerapan Projek Penguatan Profil Pelajar Pancasila Pada Pembelajaran PKn di SDN 42 Ampenan - Sri Muliati; Syudirman (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) in Civic Education (PKn) learning at SDN 42 Ampenan. Using descriptive methods and a qualitative approach, this study explores the impact of P5 on students' understanding of the material and character building. The results indicate that the implementation of P5 is effective in enhancing students' active participation through contextual learning methods, such as Problem-Based Learning (PBL), which are relevant to their daily lives. Despite challenges in implementation, such as teachers' lack of understanding and resource limitations, appropriate support and training help overcome these obstacles. This study concludes that P5 not only improves academic performance but also contributes to the development of students' character in line with the values of Pancasila, thereby preparing them to become responsible and tolerant individuals in society.